L’archéologie verticale ou l’étude des graffiti anciens : du document iconographique à la source historique (xie‑xvie siècles) - Aymeric Gaubert (Frontière·s, 2024)
The Middle Ages and the Renaissance produced a set of signs, inscriptions and graffiti that hold significance in a society of images. Such iconographic language has generated multiple uses of the wall and reveals a graffitological practice that seems normal, diversified, often devotional, but largely unknown. This graphic tradition is almost absent from classical written sources and remains to be documented, particularly by relying on the corpus preserved at the fortress of Loches in Indre-et-Loire. Despite the challenges of identification, attribution and dating, this contribution aims to demonstrate that graffiti provides an authentic voice to ancient societies, referring to past perceptions, beliefs, and practices that need to be clarified and contextualized within a true archaeology of the trace. The study of graffiti can be approached from three distinct perspectives: as a material heritage (graphic production), a cultural heritage (historical testimony), and an intangible heritage (gesture). Each of these dimensions represents a noteworthy lapidary archive, and the study of graffiti is now the subject of a developing science: graffitology.